Polarization of Pro-Environmental Tourist Behavior in Tourism Villages, Yogyakarta - Retno Darumurti; Ricky Avenzora; Tutut Sunarminto; Benny Mutiara (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
This study aimed to analyze polarization of Pro-Environtmental tourist behavior in Yogyakarta tourism village by construct behavioral process of 3 stages, pre-activity, during- activity, and post-activity. The pre-activity set from pre-perception, motivation, and preference toward village as destination choice. On-going activity observed tourist behavior along village activities, and post-activity investigate post-perception, satisfaction, and willingness to return visiting the village. The instrument of this research was closed ended questionaire, which was analyzed by One Score – One Indicator. The questionaire contains of 7 resources of ecotourism, consist of material culture, immaterial culture, nature, community activities, villagers, village atmosphere, and community economy. Data analysis using the correlation and regression statistical method. The result showed correlations among variables and its influence to destination choice. The patern of tourist behavior polarized in patern of pro-environmentally behavior. Therefore, it is necessary to build tourist perception of tourism village, develop resources and manage tourist behavior for developing rural tourism as ecotourism destination. Keywords: polarization, pro – environment, tourist behavior, tourism village